An Investigation into the Management of Online Teaching and Learning Spaces: A Case Study Involving Graduate Research Students - Jowallah, Rohan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This research evaluates the strategies implemented to support the research activities of postgraduate students pursuing online master’s programs in the University of the West Indies Open Campus, as well as the activities of their supervisors. The three main strategies employed were (1) the use of a web-based ‘teaching-learning space’ to facilitate asynchronous interaction between students and their supervisors; (2) the provision of a scheduling tool to facilitate the planning of one-on-one meetings via a synchronous web-conferencing tool; and (3) the organization of research seminars using the same web-conferencing tool. This research used Moore’s theory of transactional distance and social cognitive theoretical framework to guide the project. Moore’s model reemphasizes the need for stronger forms of communicating for online students, whereas the cognitive framework focuses on the need for social interaction among learner and teacher. Participants were graduate students (n = 34). All participants were required to complete a questionnaire online. Data were also collected from postings in discussion forums. Overall, notwithstanding limitations, the data shows there are benefits to be gained from conducting student research activities in an online environment.